P–613 Adjuvant letrozole in ovarian stimulation for in vitro fertilization does not reduce uterine peristalsis frequency prior to fresh embryo transfer. (6th August 2021) - Dreye. Holt, M; Warzecha, A K; Bülow, N S; Skouby, S O; Englund, A L M; Birc. Petersen, K; Macklon, N S
Abstract: Study question: Does adjuvant letrozole in ovarian stimulation (OS) for in vitro fertilization (IVF) decrease the uterine peristalsis frequency (UPF) prior to fresh embryo transfer (ET)? Summary answer: Adjuvant letrozole in (OS) for IVF does not reduce the UPF significantly prior to fresh ET. What is known already: Throughout the cycle UPF aids spermatozoa transport to the fallopian tube and may affect implantation. At fresh, ET UPF is negatively correlated with implantation- and clinical pregnancy rates and is believed to be modulated by estradiol and progesterone. High levels of estradiol, from multiple follicular development, in OS have been reported to increase UPF, whereas progesterone is considered to be utero-relaxant. The influence of androgens is unclear. Co-treatment with letrozole during gonadotropin OS limits the estradiol rise the supra-physiological estradiol and may therefore reduce UPF prior to fresh ET. Study design, size, duration: This single centre study was nested within a multicentre double blinded RCT investigating the impact of letrozole co-treatment during gonadotropin OS for IVF on late follicular and luteal estradiol, progesterone and testosterone levels. Between 2016 and 2017, 39 women expected normal responders were randomised to co-treatment with letrozole or placebo. Of these, 33 women completed this element of the study. The study was carried out according to the Helsinki Declaration and the ICH-Good-Clinical-Practice. Participants/materials, setting, methods: Eligible women were randomised 1:1 to adjuvant treatment with letrozole 5 mg/day or placebo in an antagonist protocol using a fixed dose of recFSH 150 IU/day. Final maturation was triggered with rhCG 6, 500 IU and luteal support with vaginal progesterone was administered from the day following oocyte aspiration. Less than one hour prior to fresh ET, six minute duration transvaginal ultrasound recordings of the uterus in sagittal section were performed and blood samples were drawn. Main results and the role of chance: A total of 33 women completed the study (letrozole n = 17; placebo n = 16). Age, BMI, and ovarian reserve markers were similar between the groups. On day of ET, serum estradiol levels were significantly suppressed in the letrozole group to mean 867 ± 827 pmol/L compared to 3, 110 ± 1, 528 pmol/L in the placebo group (P < 0.0001). Mean UPF prior to fresh ET did not differ between the intervention and control group (3.3 ± 0.36 versus 3.5 ± 0.51 per minute respectively, P = 0.108). UPF was assessed and agreed by two observers who were blind to adjuvant treatment. Two patients were excluded due to poor quality of the ultra sound recording. Supra-physiological serum estradiol in the placebo group was negatively correlated with UPF (P = 0.014; R = –0.62), but the more physiological serum estradiol levels in the letrozole group showed no correlation with UPF (P = 0.567; R = 0.15). Serum progesterone levels were similar in both groups and did not show any significant correlation with UPF. Testosterone levels were significantly higher in the letrozole group (P = 0.005) and showed a non-significant trend negatively correlated with UPF in the placebo group (P-value=0.07, R= –0.48). Limitations, reasons for caution: The limited sample size risks masking minor effects. Wider implications of the findings: The supra-physiological levels of estradiol were significantly supressed in the intervention group, but UPF prior to fresh ET was similar in both groups. UPF is not strongly correlated to luteal phase sex steroid levels. Any beneficial effect of adjuvant letrozole during OS is not through an impact of UPF. Trial registration number: NCT02939898